17-β-estradiol: a powerful modulator of blood-brain barrier BCRP activity - Hartz, Anika; Mahringer, Anne; Miller, David S; Bauer, Björn (Journal of cerebral blood flow & metabolism, 2010)
The ATP-driven efflux transporter, breast cancer resistance protein (BCRP), handles many therapeutic drugs, including chemotherapeutics, limiting their ability to cross the blood?brain barrier. This study provides new insight into rapid, nongenomic regulation of BCRP transport activity at the blood?brain barrier. Using isolated brain capillaries from rats and mice as an ex vivo blood?brain barrier model, we show that BCRP protein is highly expressed in brain capillary membranes and functionally active in intact capillaries. We show that nanomolar concentrations of 17-?-estradiol (E2) rapidly reduced BCRP transport activity in the brain capillaries. This E2-mediated effect occurred within minutes and did not involve transcription, translation, or proteasomal degradation, indicating a nongenomic mechanism. Removing E2 after 1 h fully reversed the loss of BCRP activity. Experiments using agonists and antagonists for estrogen receptor (ER)α and ER? and brain capillaries from ERα and ER? knockout mice demonstrated that E2 could signal through either receptor to reduce BCRP transport function. We speculate that this nongenomic E2-signaling pathway could potentially be used for targeting BCRP at the blood?brain barrier, in brain tumors, and in brain tumor stem cells to improve chemotherapy of the central nervous system.